Comparison of Conventional and Organic Farmers on Their Socioeconomic Characteristics and Communication Behaviors - Ismet Boz, Ayse Gul Tuncer , (International Journal of Scientific Research and Management (IJSRM), 2017)
The primary purpose of this study was to compare the conventional and organic hazelnut producers for their socioeconomic characteristics, communication behavior, and their mutual relationships with other people and organizations. Two stratified samples of 56 conventional and 42 organic hazelnut farmers from Terme district of Samsun Province were recruited as the study participants. The results showed that the organic farmers have a greater tendency to become the members offarmers’ organizations such as cooperatives and unions, carry social security mostly given to government workers and medium level state officers, and use fewer loans for the farming investments as compared to the conventional farmers. In addition, the organic farmers were more aware of the Internet and they participated in different events such as conferences, congresses, and workshops. The study concludes that in order to shorten the adoption process, farmers’ organization must be contacted first and awareness raising campaigns and adoption programs must be designed accordingly